Inhibition of the acquisition of conditioned place aversion by dopaminergic lesions of the central nucleus of the amygdala in morphine-treated rats - Xu, W; Li, Y. H; Tan, B. P; Luo, X. J; Xiao, L; Zheng, X. G; Yang, X. Y; Sui, N (Physiological research, 2012)
The negative affective state of opiate abstinence plays an important role in craving and relapse to compulsive drug use. The dopamine system participates in the reward effects of opiate use and the aversive effect of opiate abstinence. The amygdala is an essential neural substrate for associative learning of emotion. To establish a model of conditioned place aversion (CPA) in morphine-treated rats, we used different visual and tactual cues as conditioned stimuli (CS) within a conditioning apparatus. An injection of naloxone served as the unconditioned stimulus (US). The 6-hydroxydopamine (6-OHDA) lesion technique was used to investigate the effects of the dopaminergic system of the central nucleus of the amygdala (CeA) on naloxone-induced CPA. Rats were rendered physically dependent via administration of increasing doses of morphine delivered via intraperitoneal injection. Doses increased by 20 % each day for 14 days, starting from an initial dose of 6 mg/kg. All rats also received a low dose of naloxone (0.1 mg/kg) by injection 4 hours after morphine treatment on days 11 and 13 to induce CPA in a biased two-compartment conditioned place apparatus. Morphine-dependent rats with sham lesions were found to develop significant CPA after naloxone treatment. Bilateral 6-OHDA lesions of the CeA impaired the acquisition of CPA but had no effect on locomotor activity. These results suggest that the dopaminergic system of the CeA plays an important role in the negative affective state of opiate abstinence.
Keywords: Male; Cell Nucleus; potkani Sprague-Dawley; Morphine; Oxidopamine; amygdala; oxidopamin; mužské pohlaví; buněčné jádro; dopamin; krysa rodu Rattus; Dopamine; Animals; morfin; zvířata; Conditioning, Classical; narkotika; Rats; Narcotics; Amygdala; klasické podmiňování; Rats, Sprague-Dawley